Emergence of Rare Bovine-Human Reassortant DS-1-Like Rotavirus A Strains with G8P[8] Genotype in Human Patients in the Czech Republic - Moutelíková, Romana; Sauer, Pavel; Dvořáková Heroldová, Monika; Holá, Veronika; Prodělalová, Jana (Viruses, 2019)
Group A Rotaviruses (RVA) are the leading cause of acute gastroenteritis in children and a major cause of childhood mortality in low-income countries. RVAs are mostly host-specific, but interspecies transmission and reassortment between human and animal RVAs significantly contribute to their genetic diversity. We investigated the VP7 and VP4 genotypes of RVA isolated from 225 stool specimens collected from Czech patients with gastroenteritis during 2016-2019. The most abundant genotypes were G1P[8] (42.7%), G3P[8] (11.1%), G9P[8] (9.8%), G2P[4] (4.4%), G4P[8] (1.3%), G12P[8] (1.3%), and, surprisingly, G8P[8] (9.3%). Sequence analysis of G8P[8] strains revealed the highest nucleotide similarity of all Czech G8 sequences to the G8P[8] rotavirus strains that were isolated in Vietnam in 2014/2015. The whole-genome backbone of the Czech G8 strains was determined with the use of next-generation sequencing as DS-1-like. Phylogenetic analysis of all segments clustered the Czech isolates with RVA strains that were formerly described in Southeast Asia, which had emerged following genetic reassortment between bovine and human RVAs. This is the first time that bovine-human DS1-like G8P[8] strains were detected at a high rate in human patients in Central Europe. Whether the emergence of this unusual genotype reflects the establishment of a new RVA strain in the population requires the continuous monitoring of rotavirus epidemiology.
Keywords: Rotavirus; Cattle; Animals; skot; Genome, Viral; Genotype; feces; Feces; Prevalence; gastroenteritida; genom virový; RNA, Viral; Capsid Proteins; lidé; Antigens, Viral; antigeny virové; genotyp; RNA virová; Humans; Phylogeny; gastroenteritis; prevalence; G8; Rotavirus Infections; Czech Republic; virové plášťové proteiny; Central Europe; Reassortant Viruses; bovine–human reassortants; Česká republika; Gastroenteritis; zvířata; fylogeneze; rotavirus A; rotavirové infekce; reassortantní viry